2014
DOI: 10.1002/ana.24181
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced creative thinking under dopaminergic therapy in Parkinson disease

Abstract: PD patients treated with dopaminergic drugs demonstrated enhanced verbal and visual creativity as compared to neurologically healthy controls. This feature was unrelated to ICD. Dopaminergic agents might act through the reduction of latent inhibition, resulting in widening of the associative network and enriched divergent thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…This includes sudden interest in poetry (Schrag and Trimble 2001;Joutsa et al 2012), writing and embroidery (Bindler et al 2011), and painting (Chatterjee et al 2006), as well as dramatic changes in artistic style in already established artists (Kulisevsky et al 2009;Lopez-Pousa et al 2012;Shimura et al 2012). These patients also perform better than controls on tasks frequently used to estimate creative potential (Faust-Socher et al 2014). Moreover, this creative boost is lost following withdrawal of DA treatment, thus suggesting a strong link between creativity and DA medication in these patients (Bindler et al 2011;Lhommee et al 2014).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries In mentioning
confidence: 96%
“…This includes sudden interest in poetry (Schrag and Trimble 2001;Joutsa et al 2012), writing and embroidery (Bindler et al 2011), and painting (Chatterjee et al 2006), as well as dramatic changes in artistic style in already established artists (Kulisevsky et al 2009;Lopez-Pousa et al 2012;Shimura et al 2012). These patients also perform better than controls on tasks frequently used to estimate creative potential (Faust-Socher et al 2014). Moreover, this creative boost is lost following withdrawal of DA treatment, thus suggesting a strong link between creativity and DA medication in these patients (Bindler et al 2011;Lhommee et al 2014).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries In mentioning
confidence: 96%
“…Similar meaningful, creative, and collaborative endeavours [88] have been shown to improve a sense of life control and selfesteem [89]. Recent research has also indicated that people with PD taking dopaminergic drugs may demonstrate enhanced visual and verbal creativity [90], so choral singing may offer an outlet for this.…”
Section: Qol In Group Singingmentioning
confidence: 99%
“…To examine this issue, motor performance of patients with chronic stroke was measured as each played two different versions of a popular video game, one PC-based and one AR-based. The two versions required the same arm movement kinematics to control the game but differed in level of cognitive demand, which was higher with the PC approach because it uncouples a subject’s eye and hand movements and requires the subject to perform a visuospatial transform 16, 17 . Increased cognitive demand is an important consideration when designing computerized therapies to promote stroke rehabilitation 18–20 .…”
Section: Introductionmentioning
confidence: 99%